Optimal regimen of trastuzumab in combination with oxaliplatin/ capecitabine in first-line treatment of HER2-positive advanced gastric cancer (CGOG1001): a multicenter, phase II trial. Issue 1 (December 2016) - Gong, Jifang; Liu, Tianshu; Fan, Qingxia; Bai, Li; Bi, Feng; Qin, Shukui; Wang, Jinwan; Xu, Nong; Cheng, Ying; Bai, Yuxian; Liu, Wei; Wang, Liwei; et al.
Abstract Background The ToGA study showed that trastuzumab plus chemotherapy prolonged median survival in patients with human epidermal growth factor receptor 2 (HER2)-positive advanced gastric cancer. Among chemotherapy options, oxaliplatin might be as effective as cisplatin but has shown to be more tolerable. To further improve treatment options for patients with advanced gastric cancer, we initiated a study to evaluate the efficacy and safety of trastuzumab plus oxaliplatin/capecitabine in patients with HER2-positive advanced gastric cancer. Methods CGOG1001 was an open-label, multicenter, prospective phase II study. Patients with chemotherapy-naive HER2-positive advanced gastric cancer were eligible. Trastuzumab was administered at a loading dose of 8 mg/kg followed by 6 mg/kg infusion every 3 weeks (q3w). Oxaliplatin was administrated as a 130 mg/m2 infusion, q3w, for up to 6 cycles. Capecitabine 1000 mg/m2 was given orally twice daily on days 1–14 followed by a 7-day rest interval. Trastuzumab and capecitabine were continued until disease progression or intolerable toxicity. The primary endpoint was objective response rate. Simon two-stage design (H0 = 40 %, H1 = 60 %, α = 0.05, β = 0.2) by Response Evaluation Criteria In Solid Tumors 1.0 was applied. Results Fifty-one patients were enrolled. Confirmed response was recorded in 46 patients. One patient achieved complete response and 33 patients achieved partial response (response rate 34/51 [66.7 %] in the intent-to-treat population). Median follow-up time was 28.6 months, with a median progression-free survival of 9.2 months (95 % confidence interval [CI]: 6.5–11.6) and a median overall survival (OS) of 19.5 months (95 % CI: 15.5–26.0). Patients with a HER2/CEP17 ratio of greater than five achieved improved OS (20.9 vs 19.5 months, p = 0.001). The most common adverse events of grade 3 or above were thrombocytopenia (21.6 %), neutropenia (13.7 %), anemia (5.9 %) and leucopenia (3.9 %). Conclusion The addition of trastuzumab to oxaliplatin/capecitabine was well tolerated and the results demonstrated encouraging efficacy. Trial registration ClinicalTrials.govNCT01364493 .